CLASS CONFLICT OF KALI BOYONG PEOPLES IN THE NOVEL KABUT DAN MIMPI BY BUDI SARDJONO: STUDY OF MARXISM - Hussen, Muhammad (ALAYASASTRA, 2017)
Kabut dan Mimpi is a novel written by autodidact author named Budi Sardjono. The novel was published by Labuh in 2005. The novel interesting to be the object of research because its raising the issue of class conflict that occurs between the proletariat and the bourgeoisie. Forms of class conflict as to whether that appears in the novel? To determinate the class conflict that is in the novel, it will use sociology of literature approach by using a Marxist approach. Novel Kabut dan Mimpi is presenting a class struggle, but as usual, still does not happen equivalence classes as coveted proletariat.???????????????????????????????????????????????????????????????????? Keywords: novel, sociology of literature, Marxist